New contributions to the analysis of poverty : methodologial and conceptual challenges to understanding poverty from a gender perspective - Chant, Sylvia (CEPAL SantiagoCL, 2003)
Reviews the ways in which the frontiers of poverty analysis have been pushed forward and progressively 'engendered' during three decades of dedicated feminist research and activism in Latin America and other parts of the South. Focuses on barriers to understanding poverty from a gender perspective. Offers thoughts on future directions in research and policy.